# Math

posted by .

Use the functions f(x)=1/8x-3 and
g(x)=x^3 to find the indicated value or function.

(g^-1 X f^-1)(-3)

• Math -

f^-1)(-3) is the value of x that you get when f(x) = -3. That value is 0.

g^-1(0) is the value of x that you get when g(x) = 0. That is also zero.

So (g^-1*f^-1)(-3) = 0

In functional form,
f^-1(x) = 8(x+3)
g^-1(x) = x^(1/3)
(g^-1*f^-1)(x) = [8(x+3)]^1/3
2(x+3)^1/3

## Similar Questions

1. ### Algebra-Functions

I have two problems, that both have graphs involved. 1. How do use a graph to find a particular function value like y=f(x).Find 2?

3. ### math

find the numerical deriviative of the given function at the indicated point. use h=0.001. is the function differentiable at the indicated point?
4. ### Math

Use the given function values and trigonometric identities (including the relationship between a trigonometric function and its cofunction of a complementary angle) to find the indicated trigonometric functions. sec Q = 5 tan = 2sqrt6 …
5. ### Math(Correction)

Use the given function values and trigonometric identities (including the relationship between a trigonometric function and its cofunction of a complementary angle) to find the indicated trigonometric functions. Sorry for the mistake. …
6. ### Math(Correction)

Use the given function values and trigonometric identities (including the relationship between a trigonometric function and its cofunction of a complementary angle) to find the indicated trigonometric functions. sec Q = 5 tan = 2sqrt6 …
7. ### Math(Correction)

Use the given function values and trigonometric identities (including the relationship between a trigonometric function and its cofunction of a complementary angle) to find the indicated trigonometric functions. sec Q = 5 tan Q = 2sqrt6 …
8. ### math

The application of one function followed by the application of a second function to the result of the first as in F^-1(f(x)) is called composition of functions. The two functions need not be inverse of each other. In a diagram, the …